A Web-Based Flipped Classroom in Introductory Programming Education: Effects on Student Learning Outcomes - Alifya NFH; Fathahillah fathahillah; Andi Akram Nur Risal; Irwansyah Suwahyu; Fediyatun Muntazarah (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2026)
This study examined the effectiveness of a web-based flipped classroom model in improving student learning outcomes in an Algorithms and Programming course, compared with conventional instruction. A quasi-experimental pretest–posttest control group design was employed, involving 64 students from the Informatics and Computer Engineering Education Program at Universitas Negeri Makassar. The experimental group received instruction through a web-based flipped classroom model, whereas the control group received conventional lecturer-led instruction. Data were analysed using descriptive statistics, assumption testing, an independent samples t-test, normalized gain (N-Gain), and Cohen’s d effect size in R. The results showed that the experimental group achieved a higher mean post-test score (75.38) than the control group (57.81). An independent samples t-test indicated a statistically significant difference between the two groups (p < .001). The experimental group also achieved a higher N-Gain (0.499, moderate) than the control group (0.214, low), indicating greater improvement in learning outcomes under the web-based flipped classroom model. Cohen’s d was 1.058, indicating a large and educationally meaningful effect. The study concludes that the web-based flipped classroom model was effective in improving student learning outcomes in the Algorithms and Programming course. Future research should examine additional explanatory variables, such as learning motivation and self-regulated learning.